ANALISIS KEBIJAKAN PENGEMBANGAN PARIWISATA UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) SELAMA MASA PANDEMI COVID-19 DI KOTA KUPANG - Gaudensius K. Poto; Apriana Fanggidae; Maria Indriyani H. Tiwu (RJABM (Research Journal of Accounting and Business Management), 2022)
This study aims to analyze tourism development policies to increase local revenue during the Covid-19 Pandemic period in Kupang City, obtained from the Kupang City Tourism Office. Analysis of two stages is carried out; In the first stage we analyzed the tourism development policy during the Covid-19 pandemic period in Kupang City, as well as analyzing the impact of these policies on the tourism sector and the contribution of the tourism sector to regional original income using a qualitative descriptive approach. In the second stage, the priority of tourism development policies to increase local revenue during the Covid-19 Pandemic Period Analysis through Analytical Hierarchy Process (AHP). The results show that the tourism development policy during the Pandemic period is the development of Human Resources (HR) of tourism, improving the quality of the tourism industry, developing tourism attractions, developing tourism imagery, and community empowerment through tourism. The contribution of the tourism sector to local revenue is not optimal because it is still sourced from the tourism industry. With AHP, this research identifies the priority of tourism development policies to increase local revenue during the Pandemic period, namely tourism destinations, tourism marketing, tourism institutions, and the tourism industry. This study shows that the level of training, supervision, and low management of tourism, increasing the development of tourism destinations, and increasing cooperation. The basic implications of this study are to improve tourism training, supervision, and management, establish regional regulations on tourist attractions and build cooperation with private and other regions.Â Keywords: Tourism Development Policy, Regional Original RevenueÂ